Third space partnerships with students: Becoming educational together - Burns, Tom; Sinfield, Sandra Frances; Abegglen, Sandra (International Journal for Students as Partners, 2019)
This case study discusses how we harnessed a University Teaching Fellowship to open a collective third space partnership with “non-traditional” students to enable them to draw on their experiences of transition into higher education and to produce resources designed to help other students find their place, voice, and power at university. We discuss first the “in-between” opportunities of learning development as a “third space profession” that enables us to work in creative partnership with students. We further set the scene by exploring the third space potential of learning development per se and then examine the successful development and administration of a learning development module, Becomingan Educationist, at a medium-sized university in the United Kingdom.We conclude by arguing for third space partnerships not just alongside the curriculum, but in and through the curriculum as well.